Haemodynamic effects of physiotherapy programme in intensive care unit after liver transplantation - YURDALAN, SAADET UFUK (TAYLOR & FRANCIS LTD, 2010)
Objective. To determine the haemodynamic effects of intensive care physiotherapy after liver transplantation. Patients and methods. Thirteen patients were included in the study after liver transplantation. The following physiotherapy programme were applied to the patients in intensive care unit: Respiratory physiotherapy, active joint movements, sitting in bed (first task), sitting at the edge of bed (second task), standing (third task), sitting out of bed (fourth task) and walking (fifth task). Heart rate (HR), mean, systolic and diastolic blood pressures (MBP, SBP, DBP), peripheral oxygen saturation (SpO(2)), respiration rate (RR) were recorded before treatment, after each task, after treatment and at the fifth minute of recovery. Pain level was assessed with Visual Analogue Scale (0-10). Results. When compared with supine position before treatment, all of the parameters except RR increased after the first task whereas HR, SBP, MBP and pain increased after the second task. After the third task only HR and pain increased. There was no significant difference between the fourth task and pre-treatment values while HR, DBP and pain increased after the fifth task. When measurements of pre-treatment, immediately after treatment and the fifth minute of recovery were compared HR, MBP and pain increased after treatment whereas HR, RR and pain decreased after recovery. There was no significant difference between pre-treatment values and fifth minute of recovery measurements. Conclusion. Returning to initial values after a 5-min period shows that cardiopulmonary changes caused by intensive care physiotherapy after liver transplantation are responded at physiological limits.
Keywords: Liver transplantation; intensive care unit; physiotherapy; QUALITY-OF-LIFE; ABDOMINAL-SURGERY; PHYSICAL-ACTIVITY; PULMONARY COMPLICATIONS; EXERCISE; PERFORMANCE; RECIPIENTS; RESPONSES; STRESS; TRIAL